2017
DOI: 10.1002/agr.21520
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Egyptian organic agriculture: A local maximum likelihood approach

Abstract: Productive efficiency analysis is a relevant tool that can be used to evaluate differences in the performance between conventional and organic farms. Such study is important for the assessment of the economic viability of these two agricultural systems. Although the existing research has widely used the stochastic frontier methodology and the data envelopment analysis nonparametric approach to assess farming performance, the use of the local maximum likelihood (LML) approach proposed by Kumbhakar et al. is sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Besides, Flubacher [36], who compared the technical efficiency of organic and conventional dairy farms in the Swiss mountain region, highlights similar results. Conversely, some researchers revealed that the technical efficiency attained by organic farms is higher than that of conventional ones [45,46].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Besides, Flubacher [36], who compared the technical efficiency of organic and conventional dairy farms in the Swiss mountain region, highlights similar results. Conversely, some researchers revealed that the technical efficiency attained by organic farms is higher than that of conventional ones [45,46].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Com os valores dos coeficientes mais altos e sendo significativos estatisticamente, esses dados apontam para a importância de a esfera pública e as entidades do terceiro setor assistirem e orientarem os produtores da Amazônia na implementação das técnicas sustentáveis de produção, bem como o Estado garantir educação básica no meio rural. Na literatura recente de ecoeficiência, Guesmi et al (2018) e Huy & Nguyen (2019) discutem resultados similares para essas duas variáveis ao analisarem a eficiência técnica de produtores do Vietnã e do Egito, respectivamente. De fato, esse impacto positivo é amplamente verificável nos estudos do tema.…”
Section: Fatores Determinantes Da Ecoeficiênciaunclassified
“…Price efficiency is achieved when the value of marginal products is the same as the price of the factor of production concerned. Lastly, economic efficiency occurs when efforts are made to achieve technical efficiency as well as price efficiency (Guesmi et al, 2018;Anik et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%